Have a look around: the effect of physical environments on risk behaviour in work-related versus non-work related decision-making tasks. Issue 11 (2nd November 2018) - Burmeister, Carolin P.; Moskaliuk, Johannes; Cress, Ulrike
Abstract: Due to ubiquitous computing, knowledge workers do not only work in typical work-associated environments (e.g. the office) but also wherever it best suits their schedule or preferences (e.g. the park). In two experiments using laboratory and field methods, we compared decision making in work and non-work environments. We hypothesised that participants make riskier work-related decisions when in work-associated environments and riskier non-work-related decisions in non-work-associated environments. Therefore, if environment (work vs. non-work) and decision-making task (work-related vs. non-work-related) are incongruent, then risk-taking should be lower, as the decision maker might feel the situation is unusual or inappropriate. Although results do not reveal that work-associated environments generally encourage riskier work-related decisions (and likewise for non-work), we found environmental effects on decision making when including mood as a moderator. Practitioner summary: Mobile workers are required to make decisions in various environments. We assumed that decisions are more risky when they are made in a fitting environment (e.g. work-related decisions in work environments). Results of the two experiments (laboratory and field) only show an environmental effect when mood is included as a moderator.